2011
DOI: 10.1088/1674-1056/20/2/024204
|View full text |Cite
|
Sign up to set email alerts
|

Graded index profiles and loss-induced single-mode characteristics in vertical-cavity surface-emitting lasers with petal-shape holey structure

Abstract: The 850-nm oxide-confined vertical-cavity surface-emitting lasers with petal-shape holey structures are presented. An area-weighted average refractive index model is given to analyse their effective index profiles, and the graded index distribution in the holey region is demonstrated. The index step between the optical aperture and the holey region is obtained which is related merely to the etching depth. Four types of holey vertical-cavity surface-emitting lasers with different parameters are fabricated as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…In recent years, there have been a few theoretical articles dealing with the self-focusing performance of the gradient-index material, [11,12] the propagation property of the Gaussian beam, [13,14] the imaging quality enhancement of the optical coherence tomography, [15] etc. In addition, Jung et al [16] reported a numerical analysis of the gradient-index lens based optical probe.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been a few theoretical articles dealing with the self-focusing performance of the gradient-index material, [11,12] the propagation property of the Gaussian beam, [13,14] the imaging quality enhancement of the optical coherence tomography, [15] etc. In addition, Jung et al [16] reported a numerical analysis of the gradient-index lens based optical probe.…”
Section: Discussionmentioning
confidence: 99%
“…La réponse impulsionnelle globale résulte de la combinaison quadratique des deux phénomènes, qui agissent comme deux distributions indépendantes. La dispersion totale dans la fibre optique est par l'équation (4), [11].…”
Section: Effet De La Dispersion Modale Et Chromatiqueunclassified
“…The measured FFP had an approximate Gaussian distribution at a current of 33 mA with a divergence angle of only 5.4 • . Zheng et al [39,40] also proposed a single-modeintegrated microlens VCSEL based on a petal-shaped holey structure (see Fig. 3(d)), not only with high power and a low divergence angle but also with a simple fabrication without second epitaxy.…”
Section: Electric Injection Pc-vcselsmentioning
confidence: 99%